2021
DOI: 10.3390/w13081028
|View full text |Cite
|
Sign up to set email alerts
|

Forested Riparian Buffers Change the Taxonomic and Functional Composition of Stream Invertebrate Communities in Agricultural Catchments

Abstract: Riparian zones form the interface between stream and terrestrial ecosystems and play a key role through their vegetation structure in determining stream biodiversity, ecosystem functioning and regulating human impacts, such as warming, nutrient enrichment and sedimentation. We assessed how differing riparian vegetation types influence the structural and functional composition (based on species traits) of stream invertebrate communities in agricultural catchments. We characterized riparian and stream habitat co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Frontiers in Environmental Science frontiersin.org of litter residue and sediment on both sides quickly enters the stream channel during ice and snow melt (Brighenti et al, 2019). Although this process increases the turbidity of stream water, it also simultaneously transports a large amount of organic matter into the stream (Brighenti et al, 2019;Sargac et al, 2021). Climate change in the surrounding environment can affect the environmental characteristics of stream ecosystems (Brown et al, 2018;Brighenti et al, 2019), which has a significant impact on stream hydrology and water quality in particular (Lencioni et al, 2021).…”
Section: Changing Environmental Factors In Headwater Streams During I...mentioning
confidence: 99%
“…Frontiers in Environmental Science frontiersin.org of litter residue and sediment on both sides quickly enters the stream channel during ice and snow melt (Brighenti et al, 2019). Although this process increases the turbidity of stream water, it also simultaneously transports a large amount of organic matter into the stream (Brighenti et al, 2019;Sargac et al, 2021). Climate change in the surrounding environment can affect the environmental characteristics of stream ecosystems (Brown et al, 2018;Brighenti et al, 2019), which has a significant impact on stream hydrology and water quality in particular (Lencioni et al, 2021).…”
Section: Changing Environmental Factors In Headwater Streams During I...mentioning
confidence: 99%
“…Additionally, previous studies reported that riparian forests adjacent to streams directly influence the flow mechanisms of sediments, organic matter, and nutrients from watersheds [19,20]. Riparian forests have various functions, such as preventing bank erosion, reducing organic matter and nutrients, controlling water temperature, providing habitats for aquatic and terrestrial organisms, increasing ecological health and diversity, and mitigating the negative effects of land use on rivers [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. Therefore, the relationships between land cover (particularly, green and urban areas) and stream conditions need to be studied in detail to develop programs for improving the stream health and implementing stream restoration and management strategies [34].…”
Section: Introductionmentioning
confidence: 99%